Architecture for wireless sensor and actor networks control and data acquisition - Lameski, Petre; Zdravevski, Eftim; Kulakov, Andrea; Davchev, Dancho (IEEE, 2011)
Wireless Sensor and Actor Networks (WSANs) have received increased attention from the research community. This is mainly because as an extension to Wireless Sensor Networks(WSN), they have the ability to actively participate in the environment trough the actors. This however introduces new challenges as to how to transfer commands between nodes, actors and central station who may be from different manufacturers and use different communication protocols. Another important aspect is the ability of the WSAN to present the data to the interested party or to receive the command from the operator, and do this with in the simplest and most user friendly way as possible. In this paper we propose architecture for interconnection between different layers of WSANs and the central stations that would allow building a simple interface that would ease the operation with WSANs in view of Control and Data Acquisition.
Keywords: component; Wireless Sensor and Actor Networks; Remote Data Acquisition; Control Interface